Preliminary study on the preparation and characterization of novel membranes used for CO2 absorption - Lim, Siow Kee. (2013)
The hollow fiber gas-liquid membrane contactor for gas absorption is being studied as an alternative to conventional contacting equipment that removes CO2 from a gas stream. The potential advantages are the much higher interfacial area for mass transfer and reduction in costs. However, membrane wetting that leads to absorption flux decline presents a major challenge to its practical application in industry. This study explores the modification of polyetherimide (PEI) hollow fiber membranes to improve its hydrophobicity for better application in the membrane contactor. Two hollow fiber substrates, PEI A and PEI B, were provided and chemical modification of the membrane surfaces was carried out. The PEI hollow fibers were first treated with a silane coupling agent, (3-aminopropyl)trimethoxysilane (APTMS), followed by tetraethyl orthosilicate (TEOS) solution, and finally perfluoro compound perfluorodecyltriethoxysilane (PFTS) to impart hydrophobic fluorinated SiO2 nanoparticles on the membrane surface. Membrane morphology was altered as SEM observation showed that a layer of nanoparticles were successfully grafted on the membrane surface and increased the surface roughness. This corresponded to a significant improvement in the dynamic contact angles of the hollow fibers, indicating an increase in hydrophobicity compared to the unmodified membranes. A high contact angle value of 121⁰ and 123⁰ was achieved for modified PEI A and PEI B membranes respectively. The mechanical properties of the modified hollow fiber membranes were also improved.